The Role of Innovation Capability in the relationship between Entrepreneurial Leadership and Innovation Performance in the SMEs Service industry - Al-Sharif, Abdulrahman M.; Ali, Mass Hareeza; Jaharuddin, Nor Siah; Abdulsamad , Akram; Jandab, Abdulwahab (Advances in Social Sciences Research Journal, 2023)
Drawing on the resource-based view (RBV) and the dynamic capabilities view (DCV), this study aimed to investigate the mediating role of innovation capability (IC) on the relationship between entrepreneurial leadership (EL) and innovation performance (IP). Survey data were collected from 321 middle-level employees in the SME service industry. Structural equation modeling (SEM) was used to assess the proposed relationships. The empirical analysis revealed that entrepreneurial leadership impacted innovation performance directly and indirectly through the mediating role of innovation capability. The current research contributes to both RBV and DCV by proposing and empirically testing how entrepreneurial leaders affect innovation performance. The results from this research suggest that service SME managers can play a crucial role in promoting their firms' innovation capabilities, which, in turn, influences the firms' innovation performance. This study emphasizes EL's innovation effectiveness and the triggering process of innovation capability and provides various solutions for firms to demonstrate leadership and innovation practices in responding to uncertain environments.